Sustainable water resources management under population growth and agricultural development in the Kheirabad River Basin, Iran - Ghasem Layani; Mohammad Bakhshoodeh; Mansour Zibaei; Davide Viaggi (Bio-based and Applied Economics (BAE), 2021)
In this study, an integrated system dynamics model was developed for scenario analysis in sub-sectors of the Kheirabad River Basin in southwestern Iran where managing water resources is seriously challenging due to population growth and periodic drought. Afterward, the variability of water demand and supply under baseline scenario and different water demand management policies, including water conservation and water pricing, was evaluated. Findings illustrated that with increasing population and cropland area if no further demand management policies were implemented, the total water demand and withdrawal of water resources increase by more than 0.75% annually. The annual surface water availability during 2018-2030 is expected to decrease by around -1.23%. Under these circumstances, the sustainability index of the water resources system is equal to 0.703, indicating that the water system would not be able to meet the total water demand in the near future. However, the water resource sustainability index increases significantly by improving irrigation efficiency and changing crop patterns at the basin. Also, the reduction in per capita water demand and domestic water pricing under the competition structure would help to improve the sustainability index to 0.963 and 0.749, respectively.
Keywords: Q2; Q25; 330; Sustainability Index; water system; system dynamics; agriculture; food security; Kheirabad River Basin